Decentralized credit system based on blockchain and its application - Mingsheng WANG; Heyang CAO; Peiyao LI (Tongxin xuebao)
A decentralized credit system was proposed and its construction application was given.Decentralized credit system could be constructed by expanding the transaction structure of “digital currency commodity” based on block chain,expanding the function of consensus protocol and adding specific accounts.Also,the decentralized credit system was applied to the PKI enhancement and supervision system IKP so that IKP system did not need global fund in operation.Moreover,by introducing the hierarchical “virtual currency commodity” supply adjustment mechanism in the decentralized credit system to alleviate the difficulty of regulating the “virtual currency commodity” supply of “digital currency commodity” based on block chain,the precise “virtual currency commodity” supply regulation can be achieved.